In the Room With Men: A Casebook of Therapeutic Change. 2006
DOI: 10.1037/11411-008
|View full text |Cite
|
Sign up to set email alerts
|

Facing fear without losing face: Working with Asian American men.

Abstract: helped shaped my view of masculinity: my father, who took a risk to move his family to the United States, and my mother, who was the breadwinner but adhered faithfully to her ascribed cultural role to comply with the patriarch's decisions.It is not surprising that themes of leadership, decision making, and importance of the family provided an overall framework in my perception of masculinity. At the same time, values of limiting emotional expression or display, authoritarianism, and sexism also contributed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Past studies have shown face concern to be related to lower self-disclosure (Zane et al, 1998) and preference for directive counseling approach (Chou, 2000;Park, 1999). Thus counselors should be prepared to work at least initially in a more directive counseling style and establish credibility and trust with clients through culturally sensitive techniques such as gift giving and assertion of an authority role (Park, 2006;Sue & Zane, 1987). In the communication of presenting problems, coping methods, and treatment goal expectations, cognitive match is particularly important in treatment retention and outcomes (Zane et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Past studies have shown face concern to be related to lower self-disclosure (Zane et al, 1998) and preference for directive counseling approach (Chou, 2000;Park, 1999). Thus counselors should be prepared to work at least initially in a more directive counseling style and establish credibility and trust with clients through culturally sensitive techniques such as gift giving and assertion of an authority role (Park, 2006;Sue & Zane, 1987). In the communication of presenting problems, coping methods, and treatment goal expectations, cognitive match is particularly important in treatment retention and outcomes (Zane et al, 2005).…”
Section: Discussionmentioning
confidence: 99%